The Sexual Behaviors of University Students from Papua in Surabaya - Maria Clara Giyai (Health Notions, 2017)
Sexuality is the familiar topic for us in recent day. This cross sectional study aimed to analysis the sexual behaviors of university students from Papua in Surabaya, Indonesia. The subject of this research were 30 students selected by multistage sampling. The primary data directly obtained from respondents using a questionnaire, and the secondary data was obtained from the results of survey in the related institutions. The data analysis was processed using Chi-square test. Based on the results of the study concluded that peers are the most influential factor on sexual behavior of university students. Keywords: Sexual behaviors, Students university, Porn films